Desain Pembelajaran dengan Pendekatan PMRI Menggunakan Konteks Permainan Spinner pada Materi Peluang - Kurniawan, Agung; Fauziah, Anna; Luthfiana, Maria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to produce learning instructional trajectories (LIT) on material opportunities using the PMRI approach. This study uses a design research method. This study was conducted through three stages, namely preliminary experiments, design experiments and retrospective analysis. The study was conducted at SMK Negeri 2 Tugumulyo involving 6 students of class X ATP 5 in cycle 1 and 20 students of class X ATP 4 in cycle 2. Video recordings, observations, interviews, documentation, pre-tests and post-tests from pilot experiments and teaching experiments that will be analyzed by means of validity and reliability. The results of the instructional trajectory learning show that with the PMRI approach students can better understand the concept of opportunity, expected frequency, mutually exclusive and non-mutually exclusive opportunities using the context of the spinner game and can apply these concepts in solving problems in everyday life. Conclusion, the PMRI approach makes students better understand mathematical problems that are brought into everyday life problems. Keywords: PMRI, Design Research, Learning intructional trajectory